2021
DOI: 10.1093/jamia/ocaa301
|View full text |Cite
|
Sign up to set email alerts
|

The burden of the digital environment: a systematic review on organization-directed workplace interventions to mitigate physician burnout

Abstract: Objective To conduct a systematic review identifying workplace interventions that mitigate physician burnout related to the digital environment including health information technologies (eg, electronic health records) and decision support systems) with or without the application of advanced analytics for clinical care. Materials and Methods Literature published from January 1, 2007 to June 3, 2020 was systematically reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 83 publications
1
50
0
1
Order By: Relevance
“…Furthermore, it is possible to draw on the wider literature when identifying potentially useful burnout interventions. For example, there has been a growing awareness of the contribution of technology advancements and associated technology-related frustrations to increasing healthcare professional burnout [ 94 ]. However, a recent systematic review of 81 studies in physicians found that interventions which optimise technologies, such as by providing training, reducing the time spent on electronic documentation or improving workflow processes were associated with burnout reductions [ 94 ].…”
Section: Burnout Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is possible to draw on the wider literature when identifying potentially useful burnout interventions. For example, there has been a growing awareness of the contribution of technology advancements and associated technology-related frustrations to increasing healthcare professional burnout [ 94 ]. However, a recent systematic review of 81 studies in physicians found that interventions which optimise technologies, such as by providing training, reducing the time spent on electronic documentation or improving workflow processes were associated with burnout reductions [ 94 ].…”
Section: Burnout Interventionsmentioning
confidence: 99%
“…For example, there has been a growing awareness of the contribution of technology advancements and associated technology-related frustrations to increasing healthcare professional burnout [ 94 ]. However, a recent systematic review of 81 studies in physicians found that interventions which optimise technologies, such as by providing training, reducing the time spent on electronic documentation or improving workflow processes were associated with burnout reductions [ 94 ]. These interventions can be simple to identify, design and deliver, and could become increasingly beneficial in a time where medical and surgical interventions are becoming more and more digitised.…”
Section: Burnout Interventionsmentioning
confidence: 99%
“…Our study is relevant to the current global effects of the pandemic on HCPs and their daily use of technology in providing patient care within the Saudi context. Results from our study add to a growing body of evidence calling for a focus on measuring the effects of technology used by HCPs and its impact on stress and burnout [18,22,34,35].…”
Section: Discussionmentioning
confidence: 69%
“…Just as patients need expanded access to data organized into understandable dashboards, so too will healthcare teams need ready access to critical information organized into the clinical workflow. The current overwhelming deluge of information (31) as typified by the -inbox problem‖ can be ameliorated by inserting algorithms that reduce information to actionable summaries, just as the airline industry did decades ago (32).…”
Section: Picturing a Highly Functional Ecosystemmentioning
confidence: 99%